PENGARUH PRICING STRATEGY, PRODUCT QUALITY DAN SERVICE QUALITY PADA CUSTOMER SATISFACTION TERHADAP REPURCHASE INTENTION DI PT. DAIHATSU INDONESIA - Fernando, Christopher; Yusrin, Nur Amalyna (Jurnal Nusa Manajemen, 2025)
This study aims to examine the influence of pricing strategy, product quality, and service quality on customer satisfaction, as well as its impact on repurchase intention of PT. Daihatsu Indonesia customers in the Greater Jakarta area. This study is motivated by the importance of maintaining customer loyalty through satisfaction based on product quality, service, and appropriate pricing strategy, especially after the emergence of the issue of crash test manipulation scandal by Daihatsu which can affect customer perception. The method used is a quantitative method with the Structural Equation Modeling – Partial Least Square (SEM-PLS) approach. Data were collected through distributing questionnaires to 559 respondents who are Daihatsu car users, then analyzed using the SmartPLS application. The results of the study indicate that pricing strategy, product quality, and service quality have a positive effect on customer satisfaction. In addition, customer satisfaction has a positive effect on repurchase intention. Customer satisfaction is also proven to intervene in the influence of the three independent variables on repurchase intention.